Peran CELAC dalam Menangani Krisis Pangan di Haiti - Eka Safitri Minabari; Farayani Hamin (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
This research attempts to understand the role of the Community of Latin American and Caribbean States (CELAC) in carrying out the Zero Hunger program in Haiti. Compared to the other countries in Latin America and the Caribbean, Haiti is the country that has the highest poverty and malnutrition rates. This becomes the basis for CELAC to take roles in the problem. By using research methods and international concepts proposed by Clive Archer and Andre Pariera, this study produces two findings about CELAC in overcoming problems related to malnutrition in Haiti. First, CELAC plays a role as an arena an actor through the provision of the High-Level Conference and Ministerial Conference that discusses the problems in Haiti. Second, CELAC has a role as an initiator through the promotion of dialogue between countries to exchange experiences on national social programs.